Influence of aggressive media programs on student behaviour - Azizi Yahaya; Balan Rathakrishnan; DK Zainab Pg Hj Tuah; Sanju George (Indian Psychological Association, 2020)
We aimed to study the influence of aggressive content in media on student behaviour. The study sample consisted of students with disciplinary problems from three secondary schools in Kulai District, Johor, Malaysia. A total of 127 students (92 Males and 35 Females) participated in the study. A set of questionnaires, divided into parts A and B, was used to collect data. questions that have been stated to answer the questions. This questionnaire was adapted from the Attractive Media and The Effect on Audience Questionnaire developed by Heinichi, Molenda, Russel and Ely (1991). Data were analyzed using the Statistical Package for Social Sciences, Version 17.0 (SPSS). A pilot study was carried out initially. Main findings of our study were that: the influence of media programs with an aggressive content on students was moderate; and the effects on students' aggressive behaviour were also moderate. This study has important implications on the role of the media in re-evaluating the programs they broadcast for their aggressive content as such content can influence students toact aggressively.